Academic Supervision untuk Meningkatkan Learning Design Skills Guru di Sekolah Dasar - H Muhsin (Universitas Pendidikan Mandalika, 2021)
The study was conducted to determine the impact of academic supervision on improving teacher performance in the learning design process. The action research method was used to apply academic supervision and was designed in three cycles. Data were collected through 17 elementary school teachers from 10 supervisory schools in North Batukliang sub-district, Central Lombok Regency and analyzed quantitatively-descriptively. This study found that the implementation of continuous academic supervision was able to improve the learning design skills of elementary school teachers. In cycle-I as many as 41.17% of teachers have a good performance in learning design, in cycle-II there are 35.29% of teachers needing guidance, then in cycle-III all teachers meet standard skills in designing learning well (100%). The results concluded that academic supervision has a positive effect on improving teacher performance in elementary schools.